Mode of Incomplete Cross-Resistance Among Pipemidic, Piromidic, and Nalidixic Acids - Inoue, Satoru (1978)
Spontaneous mutants with various patterns of resistance to pipemidic acid (PPA), piromidic acid (PA), and nalidixic acid (NAL) were isolated from Escherichia coli K-12. Most mutants were less resistant to PPA than to PA and NAL, and some mutants resistant to PA and NAL were hypersusceptible to PPA. As for the mutants tested, resistance to the drugs was conferred by mutations at nalA and new nal genes designated as nalC and nalD, both of which were located at about 82 min on the recalibrated map. Resistance to PA and NAL was due to decreased sensitivity of the bacterial DNA synthesizing system to them and insufficient drug transport, whereas resistance to PPA was only due to the former.